2018
DOI: 10.1016/j.phro.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

A multi-centre analytical study of small field output factor calculations in radiotherapy

Abstract: An audit methodology was developed and applied for output factor (OF) calculations in radiotherapy. The auditees were asked to calculate OFs for field sizes from 10 × 10 cm 2 to 2 × 2 cm 2. Sixty five beams were audited; missing reference OFs were interpolated. The calculated OFs were in 73% of cases higher than the reference data. The smaller the field size, the higher the overestimations which were observed in the higher fraction of cases. Treatment planning systems generally overestimated OFs for small fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This difference may have resulted in the slightly large OF values shown in this study. Recent studies have investigated multi-institutional variations in TPS calculations (Chełmiński andBulski 2018, Lechner et al 2018). They collected the TPS-calculated OFs for ⩾20 mm from multiple institutions and compared the data with those reported by IROC-H.…”
Section: Discussionmentioning
confidence: 99%
“…This difference may have resulted in the slightly large OF values shown in this study. Recent studies have investigated multi-institutional variations in TPS calculations (Chełmiński andBulski 2018, Lechner et al 2018). They collected the TPS-calculated OFs for ⩾20 mm from multiple institutions and compared the data with those reported by IROC-H.…”
Section: Discussionmentioning
confidence: 99%
“…In a multi-centre analytical study of small field output factor calculations in radiotherapy reported by Krzysztof Chełmiński and Wojciech Bulski, for 2 × 2 cm 2 MLCshaped fields of Varian linacs, the differences between the treatment planning system output factors (based on collected beam data) often exceeded 5% and were below 10% [11]. In our study, these differences were -1.1% (6X) and -0.5% (6XFFF) for MLC-shaped fields, 1.3% (6X) and 2.6% (6XFFF) for jaw-shaped fields, -7.0% (6X) and -5.7% (6XFFF) for cone-shaped fields.…”
Section: E Comparison Of Output Factor Curves Between Different Collimation Systems (Trs483 Cop)mentioning
confidence: 99%
“…This has been recently addressed by the publication of the IAEA code of practice [41] but the accurate modelling of small fields and how the correct detector is used to collect the commissioning data is still challenging. Several groups [11] , [12] , [21] conducted national and multi-national audits respectively, of calculated small field output factors by comparing with standardised data published by the IROC-Houston QA center at MD Anderson [22] , [23] , [42] and found that not all centres were modelling these fields well. The audits found that the deviations increased with decreasing field size and the treatment planning system commonly overestimated in comparison with the reference data.…”
Section: Advanced Techniquesmentioning
confidence: 99%
“…Dosimetry audit is a key component in quality management programmes in radiotherapy, playing an important role in the safe implementation of new treatment modalities and techniques [1] , [2] , [3] , [4] . National and large scale audits provide data which can help to create, sustain and increase standards as well as have the potential to identify issues which may cause harm to patients, thus improving both quality and safety [1] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] . They can also help to reduce variability in dose delivered to the patient both nationally, internationally and within multi-institutional trials [3] , [13] , [14] , [15] , [16] .…”
Section: Introductionmentioning
confidence: 99%